Stem Cell As A Promising Modality In Chronic Kidney Disease Children Future Treatment - Widiasta, Ahmedz (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: End-stage kidney disease (ESKD) is the origin of chronic kidney disease (CKD), both in adults and children. The progression of CKD to ESKD often cannot be prevented, even with sophisticated and up-to-date medicines. Method: Data search was conducted by searching for articles in electronic databases, namely PubMed, ScienceDirect, Scopus, Cochrane and Google Scholar. Result: Based on the pathophysiology, the transformation from CKD to ESKD involves a process of fibrosis in the kidneys, which is extensive and persistent. Several studies in experimental animals have found that treatment with stem cells in liver cells can repair cells that have experienced fibrosis, this may be analogous to fibrosis in the kidneys. Through this library extract, we will discuss stem cells, as well as how to treat stem cells for CKD and ESKD in the future. Conclusion: There are various variations in research results on the effectiveness of stem cell therapy in CKD patients. This occurs because of differences in the baseline clinical entity of CKD. Research on stem cell therapy in children has not been well published.